Second Administrative Reforms Commission on right to information: A critical review - Guha Roy, Jaytilak (2007)
The administrative reform initiatives aim at providing an efficient, accountable, transparent and citizen-friendly administration. The traditional form of invisible government has become obsolete in this age of globalisation and liberalisation. There is an all-round demand and emphasis on free access and availability of information to the clients and stakeholders. The Right to Information Act 2005 is a landmark legislation that recognises citizens' right to information and operationalises this right by presenting procedures and mechanisms. The first report of Second ARC dedicated to right to information makes further significant recommendations to make the legislation more comprehensive and progressive. - Repr oduced.
Keywords: Right to information - India; Administrative reform - India; Right to information